2019
DOI: 10.1016/j.jiph.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and predictors of survival of MERS-CoV infections in Riyadh region, 2014–2015

Abstract: a b s t r a c tBackground: MERS-CoV emerged as a zoonotic disease in Saudi Arabia with 1437 cases as of July 2016. This study aimed at describing the epidemiology of MERS-CoV infection, clinical aspects of the disease and the determinants of survival. Methods: The medical records of Prince Mohamed Bin Abdulaziz Hospital were reviewed between April 2014 and December 2015 to identify admission and discharge with MERS-CoV. Patient's characteristics, epidemiologic and clinical data and laboratory results were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…We identified 11 studies on MERS-CoV. Three studies (324 participants) reporting MERS-CoV shedding in the upper respiratory tract 99 , 100 , 101 and four studies (93 participants) reporting MERS-CoV shedding in the lower respiratory tract 91 , 92 , 96 , 101 were included in the quantitative analysis. The mean shedding duration was 15·3 days (95% CI 11·6–19·0) in the upper respiratory tract and 16·3 days (13·8–18·9) in the lower respiratory tract ( Figure 3 , Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 11 studies on MERS-CoV. Three studies (324 participants) reporting MERS-CoV shedding in the upper respiratory tract 99 , 100 , 101 and four studies (93 participants) reporting MERS-CoV shedding in the lower respiratory tract 91 , 92 , 96 , 101 were included in the quantitative analysis. The mean shedding duration was 15·3 days (95% CI 11·6–19·0) in the upper respiratory tract and 16·3 days (13·8–18·9) in the lower respiratory tract ( Figure 3 , Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [ 3 , 63 , 65 , 67 , 72 , 77 , 80 ] reported the highest rate of urgent-start KRT use (35.0%, 95% CI: 16.8%–55.4%) in hospitalized patients with MERS. The mortality rate of urgent-start KRT patients with MERS was 85.5% (95% CI: 78.9%–91.2%) in four studies [ 65 , 67 , 72 , 80 ]. The use of urgent-start KRT was also associated with a higher risk of mortality in MERS patients (Four studies [ 65 , 67 , 72 , 80 ], OR 4.56, 95% CI 1.49 to 13.90, p = 0.008; I 2 = 93%, p < 0.00001, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…55 Complete resolution in the chest CT could be observed only at 4 weeks or longer after the onset of symptoms. 22,56 The radiological manifestation should be tracked until the complete resolution of pulmonary lesions in chest radiographs or CT scanning. [57][58][59][60] In the rehabilitation period, fibrotic changes in the lungs did not resolve in some patients.…”
Section: Radiology and Pulmonary Function In Surveillancementioning
confidence: 99%
“…A significantly greater number of intensive care unit admission days, older age, higher chest radiographic scores, chest radiographic deterioration patterns, and peak lactate dehydrogenase levels were observed in patients with lung fibrosis 55 . Complete resolution in the chest CT could be observed only at 4 weeks or longer after the onset of symptoms 22,56 . The radiological manifestation should be tracked until the complete resolution of pulmonary lesions in chest radiographs or CT scanning 57‐60 …”
Section: The Follow‐up Strategiesmentioning
confidence: 99%